(untitled) (Transport systems and technologies, 2019)
The article is devoted to the review of the design of test benches on which mechanical reducers are being tested, which are part of various vehicles for the movement of goods and passengers. The main attention is paid to test benches that are used by railway transport enterprises in the post-Soviet space. The authors focused on the analysis of the technical characteristics of test benches, on which mechanical reducers of the generator drive from the middle part of the wheelset axle of passenger cars operated on passenger railway cars running at speeds up to 160 km / h are tested. It has been established that in most cases (up to 70%) stand constructions were made using the element base and industry achievements of the 80s. This became an obstacle for further improvement of test methods with the use of outdated measuring equipment, which are built into the stands. The identified technical shortcomings of the existing test benches and the inconsistency of the quality of the tests of mechanical reducers with the updated requirements of European standards. This encourages the modernization of test benches. In the article, the authors indicate the main directions of improvement of the existing equipment for testing mechanical reducer, in particular, improving the design of the electric drive of the stand, and also proposed to automate the technological process of testing. The modernization directions proposed by the authors will improve the quality of bench tests of mechanical reducer.